Sasha and Emma: The Anarchist Odyssey of Alexander Berkman and Emma Goldman - Palmer, Bryan D. (Labour / Le Travail, 2013)
The article reviews the book, "Sasha and Emma: The Anarchist Odyssey of Alexander Berkman and Emma Goldman," by Paul Avrich and Karen Avrich.
Keywords: AVRICH; Karen; AVRICH; Paul; BERKMAN; Alexander; 1870-1936; GOLDMAN; Emma; 1869-1940; Nonfiction; SASHA & Emma: The Anarchist Odyssey of Alexander Berkman & Emma Goldman (Book)